2020
DOI: 10.1099/mgen.0.000480
|View full text |Cite
|
Sign up to set email alerts
|

Sudden emergence of a Neisseria gonorrhoeae clade with reduced susceptibility to extended-spectrum cephalosporins, Norway

Abstract: Neisseria gonorrhoeae multilocus sequence type (ST)-7827 emerged in a dramatic fashion in Norway in the period 2016–2018. Here, we aim to shed light on the provenance and expansion of this ST. ST-7827 was found to be polyphyletic, but the majority of members belonged to a monophyletic clade we termed PopPUNK cluster 7827 (PC-7827). In Norway, both PC-7827 and ST-7827 isolates were almost exclusively isolated from men. Phylogeographical analyses demonstrated an Asian ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The clonal timed phylogenetic analysis of ST-9363 genogroup gonococci for a global collection of 1,978 isolates from 1996 to 2018 (Table S1) estimated a substitution rate of 4.752 x 10 -6 substitutions per site per year, (95% highest posterior density (HPD) ranging from 4.163 x 10 -6 to 4.933 x 10 -6 ), which was similar to previous estimates from other population level studies that included gonococcal isolates from a single or similar STs (Sánchez-Busó et al 2019;Osnes et al 2020;Osnes et al 2021). The time to the most recent common ancestor (tMRCA) of the entire ST-9363 genogroup was estimated to be in the mid-19th century (1853; 95% highest posterior density (HPD): [1833 -1883]).…”
Section: Time-resolved Phylogenetic Inferences and Antimicrobial Resistance Variants For St-9363 Genogroupsupporting
confidence: 81%
See 2 more Smart Citations
“…The clonal timed phylogenetic analysis of ST-9363 genogroup gonococci for a global collection of 1,978 isolates from 1996 to 2018 (Table S1) estimated a substitution rate of 4.752 x 10 -6 substitutions per site per year, (95% highest posterior density (HPD) ranging from 4.163 x 10 -6 to 4.933 x 10 -6 ), which was similar to previous estimates from other population level studies that included gonococcal isolates from a single or similar STs (Sánchez-Busó et al 2019;Osnes et al 2020;Osnes et al 2021). The time to the most recent common ancestor (tMRCA) of the entire ST-9363 genogroup was estimated to be in the mid-19th century (1853; 95% highest posterior density (HPD): [1833 -1883]).…”
Section: Time-resolved Phylogenetic Inferences and Antimicrobial Resistance Variants For St-9363 Genogroupsupporting
confidence: 81%
“…Obtaining representative samples for the global ST-9363 gonococcal population is often a challenge. Convenient sampling by incorporating all available unique genomes from a genogroup along with the use of robust evolutionary models similar to this study and other genome-based gonococcal evolutionary analysis (Osnes et al 2020;Osnes et al 2021) are appropriate to estimate global evolutionary trends, although it might be inadequate for estimating incidence or prevalence of these strains. Our analyses performed on a down-sampled geographically balanced dataset largely identified the same evolutionary trends similar to the findings inferred using the full dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When this strain emerged in Norway during 2016–18 it was associated with reduced susceptibility to cephalosporins and we now confirm that the same emergence has occurred in the Netherlands during the last 3 years. 12 Since recent isolates from other European countries are scarce, these results can only suggest circulation of this strain in other parts of Europe.…”
Section: Discussionmentioning
confidence: 98%
“…Isolates belonging to MLST1901/NG-MAST1407 with mosaic penA alleles were highly prevalent among strains with reduced susceptibility to ceftriaxone also, suggesting that tracking this strain is most important for monitoring emerging resistance. However, Osnes et al 12 recently reported the emergence of a strain with reduced susceptibility between 2016 and 2018 in Norway, belonging to MLST7827 and carrying a non-mosaic penA 13.001 allele with A501V mutation. They showed that this strain, with an alarming antimicrobial resistance profile, likely originated from Asia and potentially circulates in Europe.…”
Section: Introductionmentioning
confidence: 99%